If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -8) + -4(x + 1) + -16x = 0 Reorder the terms: 5(-8 + 3x) + -4(x + 1) + -16x = 0 (-8 * 5 + 3x * 5) + -4(x + 1) + -16x = 0 (-40 + 15x) + -4(x + 1) + -16x = 0 Reorder the terms: -40 + 15x + -4(1 + x) + -16x = 0 -40 + 15x + (1 * -4 + x * -4) + -16x = 0 -40 + 15x + (-4 + -4x) + -16x = 0 Reorder the terms: -40 + -4 + 15x + -4x + -16x = 0 Combine like terms: -40 + -4 = -44 -44 + 15x + -4x + -16x = 0 Combine like terms: 15x + -4x = 11x -44 + 11x + -16x = 0 Combine like terms: 11x + -16x = -5x -44 + -5x = 0 Solving -44 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + -5x = 0 + 44 Combine like terms: -44 + 44 = 0 0 + -5x = 0 + 44 -5x = 0 + 44 Combine like terms: 0 + 44 = 44 -5x = 44 Divide each side by '-5'. x = -8.8 Simplifying x = -8.8
| H/4=8 | | n/14=20/30 | | 5s^2-14s-3= | | a^2/a^16 | | X=8-42i | | (3n+3)-(12n-5)= | | 11+(-25)= | | 26-3t=-30 | | 8x-12=6x+26 | | 8x=8+4x | | 8x-49=x | | -3/4x--2=-8 | | -3(t-6)-(t+8)=9 | | 9=2z+6 | | 9(6+5h)= | | 5v^2-v-20=4v^2 | | 0=(7x-8)(7x+9) | | 42x^2+138-120=0 | | 0-2=-1 | | -35f+40=25f | | 3x-9=3(x+6) | | -12+7+(-2)= | | 5t^2=28y | | -0.8-8=0.2a | | 5.64+x=10 | | 26-8t=-3 | | -4=n+3 | | 35f+40=25f | | 16=d-2/14 | | 1+4(x-4)=3-2(x-3) | | 2b-7=8-3b | | X=-3*5/6-4 |